Transformational Leadership and Its Influence on Employee Performance in Multinational Corporation - Andi Gazly Satrya Amal; Sugiyanto Sugiyanto; Maurits Sipahutar (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Employee performance is widely recognized as a key determinant of organizational success. High-performing employees contribute to productivity, innovation, service quality, and competitive advantage, which are essential for multinational corporations operating in highly competitive global markets. This study adopts a qualitative research approach using a literature review (library research) method to examine the influence of transformational leadership on employee performance in multinational corporations. This study concludes that transformational leadership plays a significant and positive role in enhancing employee performance in multinational corporations. Based on the results and discussion, it is evident that transformational leadership not only improves employees’ task performance but also strengthens contextual and adaptive performance, which are crucial in complex and culturally diverse organizational environments.